2019
DOI: 10.7717/peerj.6821
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional assessment, phytochemical composition and antioxidant analysis of the pulp and seed of medjool date grown in Mexico

Abstract: The aim of this study was the characterization of fatty acids, antioxidant activity, some physical properties, nutrient content, sugars, and minerals in the pulp and seeds of the date cultivar ‘Medjool’ (Phoenix dactylifera L.) grown in Mexico. The samples were obtained at maturity (Tamar) in the 2017 harvest season in the valleys of San Luis Rio Colorado and Mexicali, Mexico. The following average values were obtained on a % dry weight basis for pulp and seeds, respectively: protein, 3.14% and 4.84%; lipids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…This may be attributed to the high concentration of polyphenols being released. These findings are consistent with the research conducted by Salomón-Torres et al ( 62 ) who reported that the seed of “Medjool” dates has polyphenolic content 10 times greater than that found in the pulp. The study by Saleh et al ( 63 ) revealed a similar trend; they claimed that the date palm may contain water-soluble phenolic compounds.…”
Section: Resultssupporting
confidence: 93%
“…This may be attributed to the high concentration of polyphenols being released. These findings are consistent with the research conducted by Salomón-Torres et al ( 62 ) who reported that the seed of “Medjool” dates has polyphenolic content 10 times greater than that found in the pulp. The study by Saleh et al ( 63 ) revealed a similar trend; they claimed that the date palm may contain water-soluble phenolic compounds.…”
Section: Resultssupporting
confidence: 93%
“…In addition, research has also been conducted to explore the beneficial antioxidant effects of date seeds based on their rich source of phenolic compounds [ 34 ]. Salomón-Torres and colleagues (2019) found that the polyphenolic content in the seed of ‘Medjool’ dates is ten times higher than that in the pulp [ 35 ]. Presence of phenolic compounds such as tannins, flavonoids, saponins, anthraquinones, and coumarins agreed with the Shinoda assay contributed to the antioxidant properties of date seeds, resulting in a lower IC 50 of 0.0046 g/L by employing 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical method.…”
Section: Biological Activities Of Date Seedsmentioning
confidence: 99%
“…Data on the planted and producing area of date production and date crop production in Mexico in the period 1980 to 2018 were obtained from the agricultural statistical information system of Mexico (SIAP, 2018). The date seed was estimated as accounting for 5.67% of the total mass of date fruit (Salomón-Torres et al, 2019). The mass of date seeds produced was subsequently estimated through Equation ( 10).…”
Section: Date Production and Data Collectionmentioning
confidence: 99%